PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN MENABUNG NASABAH. BCA Syariah Cabang Jakarta Barat - Raniah Alifah (2020)
This research is a quantitative study that aims to determine the effect of brand image and product quality on customer decisions. The population in this study were respondents who already had BCA Syariah savings in the West Jakarta Branch with a sample of 50 respondents. The sample selection is done based on several predetermined criteria. With the method of non probability sampling (purposive sampling). Data collection is done by distributing questionnaires through Google Form. This research uses descriptive analysis with index scale and hypothesis testing using individual statistical tests with SmartPLS 3.0 (Partial Least Square) software program and the significance level of 0.05 or 5%. The results of SmartPLS 3.0 testing show that (1) there is a significant influence of brand image on customer decisions with a path coefficient of 0.268. (2) there is a significant influence of product quality on customer decisions with a path coefficient of 0.700